INTERNATIONALIZATION OF INNOVATION IN SMEs AS A STRATEGIC CHOICE THE CZECH CASE - Awakowicz, Bartosch (2012)
With the growing competition both on domestic and on international markets, SMEs face very specific challenges to sustain in their activity. A strategy to gain a competitive edge can be to internationalize innovative activities. In this work the internationalization of innovation is reflected in the context of SMEs. This is done in the first step by making a connection between research on SMEs, on Internationalization and on R&D and subsequently building a theoretical framework. In the second step, the innovative activity of a Swiss firm's Czech subsidiary is investigated on a case-study basis from the perspective of the suggested theoretical framework. The main contribution of this work to research is that it puts in a research field, which is dominated by large enterprises, the focus on SMEs.